Normal impact of sand particles with solar panel glass surfaces. (October 2016) - Humood, Mohammad; Beheshti, Ali; Meyer, Jacob L.; Polycarpou, Andreas A.
Abstract: An analytical elasto-plastic model coupled with a transient impact model is developed to study single normal impact of small sand particles on solar panels glass surfaces. Nanoindentation measurements are performed on two commercial photovoltaic protective glasses, namely annealed and tempered, to extract their mechanical properties required for the impact model. The model is qualitatively validated through sandblasting experiments. Evaluation of the impacting sites using scanning electron microscopy shows significant plastic impressions of Vickers-like indentation for small sand particle impact. Employing the analytical model, parametric study is performed to examine the glass deformation due to single sand impact using different corner radii, impact speeds and glass types. The proposed model is used to predict plastic damage due to normal sand impact. Highlights: Analytical model for normal sand particle impact. Experiment sand particle impact on solar glass surfaces. Vickers-like indentation impressions for small particle impact on glass. Parametric study of influence of corner radii, impact speeds and glass types. Thermal tempering of solar glass shows enhanced impact damage resistance.